ANALISIS PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PENGGUNA JASA PENGIRIMAN (Study Kasus Pada Pengguna Jasa JNE Express Across Nations Cabang Nganjuk) - Altofu Rohman; Aglis Andhita Hatmawan (UNIVERSITAS PGRI MADIUN, 2017)
This study aims to determine the effect of brand image and service quality on the decision to use the services of PT JNE in Nganjuk city. The research method used is quantitative research method with descriptive research type. The decision to use services (Y) is a dependent variable, while brand image (X1) and service quality (X2) are independent variables. Sampling technique using Accidental sampling technique is the form of sampling based on coincidence where, anyone who happens to meet with the researcher and considered suitable to be the source of data that will be the sample of this study. From the research result, it can be seen that multiple linear regression equation coefficient value of brand image 2,833 and value of service quality coefficient 5,316 and variable of brand image strategy (X1) have significant influence to decision using JNE (Y) service equal to 56,55% and service quality variable (X2) Significant effect on the decision to use JNE (Y) service equal to 67,77%, meaning that brand image and service quality equally influence to decision using JNE services. In the t test it can be said that if the brand image is increased 1% or one unit, it can improve the decision using JNE services of 53.9%, while if the quality of service increased 1% or one unit, it can increase the decision using services of 47 %. In the F test, the value of F arithmetic is 2.833. Because F arithmetic> F table (2.833> 0.677), it can be concluded that the model used is correct. When viewed from probability, where the probability (0,000) <significance level (0.05), then the equation model Y = a + b1X1 + b2X2 used is acceptable. This shows the effect of independent variables (brand image and service quality) simultaneously significant to delivery decisions, whereby the higher the influence of brand image on the decision to use services and the higher the quality of service, the decision to use services will increase and increase. The brand image is offered in accordance with the quality of services offered so that the decision to use is increasing.Keywords: brand image and service quality, decision using JNE services.